Sistem Informasi Sistem Perangkap Hama Tikus Di Kandang Ayam Berbasis Iot Menggunakan Metode C.45 - faritcan, timbo; Faritcan Siallagan, Timbo; Andrian, Avit (Jurnal Manajemen Sistem Informasi (JMASIF), 2022)
Mice are animals that can interfere in people's lives. The nature of rats that always make runways, are very sensitive to bait, or are very familiar with their environment. When humans are sometimes negligent, that's when rats can change the existing environmental conditions according to their habitat. Rats really like to live in areas that are rarely touched by humans, such as in dark, damp, dirty, hidden places, near food sources and difficult to reach by humans. These animals are sometimes disturbing. After conducting this research authors found that this tool is able to reduce pests. rats around the chicken coop by means of automatic traps The research was conducted using the C4.5 Algorithm calculation method in which this method is used to perform calculations in order to determine decisions where parameters are calculated in order to see how many rats enter the trap. With this system, it can reduce rats that roam the house or in buildings where archives are stored which can interfere with people's lives. The object of this research is made in a chicken coop where you can see the number of rats that interfere with chicken hatching. For this reason, this research system is designed to reduce rat pests in chicken coops by using traps and will result in a reduction of rats in chicken coops and become a tool that people can use to deal with rat infestations.